aFGF Targeted Mediated by Novel Nanoparticles-Microbubble Complex Combined With Ultrasound-Targeted Microbubble Destruction attenuates Doxorubicin-Induced Heart Failure via Anti-Apoptosis and Promoting Cardiac Angiogenesis - Nan-Qian Zhou; Nan-Qian Zhou; Nan-Qian Zhou; Zhi-Xin Fang; Zhi-Xin Fang; Zhi-Xin Fang; Ning Huang; Ning Huang; Ning Huang; Yue Zuo; Yue Qiu; Yue Qiu; et al. (Frontiers Media S.A., 2021)
The purpose of this study was to evaluate the protective effect of acidic fibroblast growth factor targeted mediated by novel nanoparticles-cationic lipid microbubbles complex (aFGF-NP + CPMBs) combined with ultrasound targeted microbubble destruction (UTMD)on doxorubicin-induced heart failure (HF)and its mechanism. Heart failure rats induced by intraperitoneal injection with doxorubicin (DOX) to achieve cummulative dose of 15mg/kg for continuous 6 weeks showed left ventricular dysfunction, seriously oxidative stress, cardiomyocyte apoptosis, and decrease of myocardial vascular density. In contrast, aFGF-NP + CPMBs combined with UTMD therapy (3ug/kg, caudal vein injection, twice a week, 6weeks)prominently ameliorated left ventricular dysfunction by increased ejection fraction (EF) and fractional shortening (FS), decreased brain natriuretic peptide (BNP); strengthened the ability of antioxidant stress confirmed by increasing the activity of SOD and reducing the production of MDA; exerted the effect of anti-cardiomyocyte apoptosis and promotion angiogenesis by inhibited Bax expression and increased Bcl-2 expression and platelet endothelial cell adhesion molecule (CD31) expression. Taken together, the research suggested that aFGF targeted mediated by novel nanoparticles-cationic lipid microbubbles complex combined with UTMD should be a promising targeted treatment for heart failure.